2022
DOI: 10.1093/braincomms/fcac044
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic junctional adhesion molecule-A regulates T-cell entry past the glia limitans to promote central nervous system autoimmune attack

Abstract: Contact mediated interactions between the astrocytic endfeet and infiltrating immune cells within the perivascular space are underexplored, yet represent potential regulatory check-points against CNS autoimmune disease and disability. Reactive astrocytes upregulate Junctional Adhesion Molecule-A (JAM-A), an immunoglobulin-like cell surface receptor that binds to T cells via its ligand, the integrin, lymphocyte function-associated antigen-1. Here, we tested the role of astrocytic JAM-A in regulating CNS autoinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Furthermore, as previously observed on endothelial cells, inflammatory stimuli release JAM‐A from the astrocyte tight junctions, leading to a more dispersed cell surface expression and making JAM‐A accessible for engagement by immune cells [48]. Mice lacking JAM‐A specifically in astrocytes were observed to develop ameliorated aEAE by trapping T cells in PVS underscoring a role for JAM‐A in mediating T‐cell migration across the perivascular glia limitans [48]. Lack of JAM‐A in astrocytes cocultured with T cells revealed a decrease of the inflammatory effector molecules such as CCL2, GM‐CSF, and MMP‐2, with proven roles in immune cell entry into the CNS parenchyma during EAE [48].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Furthermore, as previously observed on endothelial cells, inflammatory stimuli release JAM‐A from the astrocyte tight junctions, leading to a more dispersed cell surface expression and making JAM‐A accessible for engagement by immune cells [48]. Mice lacking JAM‐A specifically in astrocytes were observed to develop ameliorated aEAE by trapping T cells in PVS underscoring a role for JAM‐A in mediating T‐cell migration across the perivascular glia limitans [48]. Lack of JAM‐A in astrocytes cocultured with T cells revealed a decrease of the inflammatory effector molecules such as CCL2, GM‐CSF, and MMP‐2, with proven roles in immune cell entry into the CNS parenchyma during EAE [48].…”
Section: Discussionmentioning
confidence: 70%
“…JAM‐A expression on astrocytes was previously shown to contribute to T‐cell migration across the glia limitans into the CNS parenchyma [48]. This second step in immune cell migration across the glia limitans into the CNS parenchyma is crucial for inducing clinial disease in EAE in C57BL/6J mice [49].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent work in EAE also showed that junctional adhesion molecule-A (JAM-A), in addition to its function as a tight junction, also plays a role in astrocyte-T cell communication and promotes the passage of the latter from the perivascular space into the parenchyma ( 76 ).…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%